2008
DOI: 10.1002/chem.200801398
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Biological Activity of Neopeltolide and Analogues

Abstract: Combining the core structure of neopeltolide, lactone 16 a, with the oxazole-containing side chain 23 via a Mitsunobu reaction provided the cytotoxic natural product neopeltolide (2). The side chain 23 was prepared from oxazolone 24 via the corresponding triflate. Key steps in the preparation of 23 were a Sonogashira coupling, an enamine alkylation, and a Still-Gennari Horner-Emmons reaction. By changing the Leighton reagent in the allylation step, the 11-epimer of lactone 16 a, compound 50 was prepared. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 86 publications
5
45
0
Order By: Relevance
“…As with elimination of the oxazole-containing side chain, substitution of this native portion with the octanoyl ( 45 ) or benzoyl ( 44 ) groups also abolished the vast majority of activity, with growth inhibition observed at only the maximum concentration: 10 μ M of the octanoyl ester inhibits 25% of P-388 cell growth and 33% of MCF-7 cell growth, while the benzyl ester is somewhat more effective at the same concentration and inhibits 75% and 78%, respectively. It has been shown that the olefin in the side chain, which is approximated in the benzoyl ester ( 44 ) but not the octanoyl ester ( 45 ), plays a significant role in inhibiting proliferation 53. Both the octanoyl and benzoyl side chains are also significantly shorter in length than the natural side chain.…”
Section: Resultsmentioning
confidence: 99%
“…As with elimination of the oxazole-containing side chain, substitution of this native portion with the octanoyl ( 45 ) or benzoyl ( 44 ) groups also abolished the vast majority of activity, with growth inhibition observed at only the maximum concentration: 10 μ M of the octanoyl ester inhibits 25% of P-388 cell growth and 33% of MCF-7 cell growth, while the benzyl ester is somewhat more effective at the same concentration and inhibits 75% and 78%, respectively. It has been shown that the olefin in the side chain, which is approximated in the benzoyl ester ( 44 ) but not the octanoyl ester ( 45 ), plays a significant role in inhibiting proliferation 53. Both the octanoyl and benzoyl side chains are also significantly shorter in length than the natural side chain.…”
Section: Resultsmentioning
confidence: 99%
“…[12] As summarized in Scheme 3, starting from aldehyde 26 , which was synthesized from Noyori asymmetric hydrogenation followed by DIBAL-H reduction, a Leighton asymmetric allylation[13] was used to synthesize compound 28 with the C 11 stereocenter. After 28 was converted to α,β-unsaturated thioester 29 , a Feringa-Minnaard reaction enabled the introduction of the C 9 methyl group in a stereoselective manner.…”
Section: Synthesismentioning
confidence: 99%
“…100 Neopeltolide, a marine polyketide isolated from a sponge by Wright and coworkers at Harbor Branch, has shown strong antifungal and cytoxic activity and thus became of interest to synthetic chemists. [101][102][103][104][105][106][107][108][109] Reaction of the ether transfer product with methyl propiolate in the presence of phosphine lead to the formation of b-alkoxyacrylate 136. Subsequent radical-mediated cyclization stereoselectively provides the 4-alkoxy-2,6-cis-trisubstituted pyran.…”
Section: Formation Of 13-diol Ethersmentioning
confidence: 99%